Optimization of fermentation factors to enhance rice straw degradation ability using a microbial consortium LZF-12 - Zheng, Guoxiang; Zhou, Chenyang; Yin, Ting; Lu, Zhaoxin; Ai, Shuang (International Journal of Agricultural and Biological Engineering, 2019)
Biological pretreatment has broad application prospects in agricultural waste treatment because of its economic, environmental protection and energy saving characteristics. In this study, a microbial consortium LZF-12 was applied as a biological pretreatment to degrade rice straw. Batch experiments were performed to hydrolysis conditions by using the method of Box-Behnken factorial design (BBD). The results showed that the model multiple correlation coefficient R2 was 0.9816, and the effects of three factors on the degradation of rice straw of LZF-12 as descending order were the initial rice content, chicken manure content, and initial pH. The interaction between straw concentration, chicken manure concentration, and initial pH had significant effects on the degradation of a microbial consortium. Under the optimum conditions of 0.86% rice straw, 0.5% chicken manure and the initial pH of 7.0, the degradation rate of rice straw reached 72.4%. There is only small difference of 0.55% between the experimental value and predicted value from BBD model. Therefore, it is feasible for the established model due to the consistent results between the prediction and experimental value. The microbial consortium LZF-12 has high cellulase enzyme activities and degradation ability over a wide range of temperature and pH, indicating it has a good development potential and application prospects in waste biodegradation and biomass energy production.Keywords: microbial consortium, biological pretreatment, biodegradation, rice straw, optimizationDOI: 10.25165/j.ijabe.20191203.4638Citation: Zheng G X, Zhou C Y, Yin T, Lu Z X, Ai S. Optimization of fermentation factors to enhance rice straw degradation ability using a microbial consortium LZF-12. Int J Agric & Biol Eng, 2019; 12(3): 168–173.